Measurement of construction productivity : application and computer simulation - Cheang, Yew Kee. (2009)
This research work deals with the analyses of the productivities of three of the main trades involved in the construction industry. The three trades that are being studied are (i) bar bending and fixing (ii) concreting (iii) formworking. The quantities produced in each trade divided by the amount of labour used will give the basic productivity for the trade of the particular period in study.